P03.14 New features of modern 3D conformal external radiotherapy (RT) of benign head tumors in children. (6th September 2019) - Antonenko, F; Slobina, E; Abbasova, E; Smyslov, A; Dykina, A; Sidibe, N; Abdullaeva, S; Vasilyev, V
Abstract: BACKGROUND: demonstrate the possibilities of radiation therapy (LT) in children with benign head tumors using IMRT, VMAT, IGRT techniques - high-precision modern 3D conformal radiation therapy MATERIAL AND METHODS: From 1990 to 2007 for the first time in Russia, 88 children with juvenile angiofibromas were treated in Russian Scientific Center of Roentgenoradiology. The studies were carried out on the gamma-therapeutic apparatus "AGAT-P1" and on the linear accelerator "Phillips SL75" Total dose was 35–45 Gy. In 2014–2018 we treated 29 patients aged 3–17 years with benign tumors of the skull base and brain (angiofibromas, craniopharyngiomas, hemangiomas) using high-precision techniques (IMRT, VMAT, IGRT). 15 of 29 patients were repeatedly operated in various domestic and foreign clinics and were admitted to RT with the threat of bleeding, with recurrent growth of tumors, including after multiple selective angioembolization. RESULTS: Up to 80% of patients had a 5-year stable remission, and the optimal total dose for radiation therapy of benign head tumors in children was scientifically substantiated. It was found that there is a high risk of continued growth after RT in children under 8 years of age, complications in 10% of patients in the coming years after RT and in 100% of those reirradiated. In all 29 cases of RT in children, we observed a positive clinical effect - stopping bleeding from the nasopharynx after 1–3 sessions of 3D conformal RT (Dose per fraction 1.8 Gy, total dose 45–54 Gy), positive clinical symptoms under the supervision of an Head and Neck surgeon. The effect of hardening and stopping the growth of tumors according to MRI data were followed up after 3 months, 6 months, 1 year. CONCLUSION: The development of navigational, endosurgical and fibro-endoscopic minimally invasive technologies in the last 30 years has allowed to expand the indications for surgical methods of treatment for benign head tumors in children, which has reduced their flow to RT. However, after modern surgical interventions, 6–10% of these patients experience recurrences and bleeding, the number of which can be reduced with timely RT. New technologies in LT provide minimal impact on surrounding healthy tissues and allow wider use of RT in recurrent and difficult-to-reach benign skull base tumors in children